Formation of the creative position of the future teachers of chemistry and biology during training (Pedagogy of Higher and Secondary Education, 2014)
Chuvasova N. А. Formation of the creative position of the future teachers of chemistry and biology during training.On the basis of comparison, comparison, synthesis of scientific information phenomenon of «creative», «creativity», «professional position», «creative attitude» discusses various approaches to the definition of these concepts. Author determined creative quality factors, conditions and stages of the creative position of the future teachers of chemistry and biology.
Keywords: creative; creativity; professional attitude; creative positio